Peformance Analysis of Automatic Voltage Regulator (AVR) as a 3-Phase AC Generator Excitation Voltage Supply Controller: Analisis Kinerja Automatic Voltage Regulator (Avr) Sebagai Pengontrol Suplai Tegangan Eksitasi Generator Ac 3 Phasa - Liliana, Liliana (Indonesian Journal of Electrical Engineering and Renewable Energy (IJEERE), 2021)
The voltage generated by the generator will always change due to the fluctuating load. The output voltage must be kept constant within the desired value to ensure the supply of generator output power to meet the load requirements, a device called an AVR (Automatic Voltage Regulator) is needed. AVR aims to regulate the amount of excitation current supplied to the generator and the amount of excitation current is directly proportional to the amount of voltage generated by the generator. This study aims to analyze the performance of the AVR in maintaining the stability of the generator output voltage and power. Monitoring the performance of the AVR installed on the generator is carried out for 31 days. The results of monitoring and analysis after the generator installed AVR, it can be seen that the output voltage is in stability with a variation in the value between 11.59 kV to 11.8 kV while the generator output power is also still in stability with a variation in values ??between 38.1 MW to 38.3 MW. Keywords: generator, Automatic Voltage Regulator, excitation current, output voltage, output power